Infants’ and Toddlers’ Language, Math and Socio-Emotional Development: Evidence for Reciprocal Relations and Differential Gender and Age Effects - Slot, Pauline L.; Bleses, Dorthe; Jensen, Peter (Frontiers in Psychology, 2020)
Toddlerhood is characterized by rapid development in several domains, such as language, socio-emotional behavior and emerging math skills all of which are important precursors of school readiness. However, little is known about how these skills develop over time and how they may be interrelated. The current study investigates young children’s development at two time points, with about seven months in between, assessing their language, social emotional and math language and numeracy skills with teacher ratings. The sample includes 577 children from 18 until 36 months of age of 86 day care classrooms. The results of the autoregressive path analyses showed moderate to strong stability of language, socio-emotional and math language and numeracy skills, although the magnitude of associations was smaller for the latter. The cross-lagged path analyses highlighted the importance of language and socio-emotional skills for development in the other domains. Differential relations were found for the autoregressive and cross-lagged paths depending on gender and age. Language skills appeared a stronger predictor of boys’ socio-emotional and math language and numeracy skill development compared to girls. Girls’ socio-emotional skills predicted growth in math. For boys, socio-emotional and math skills appeared to be unrelated. Language skills showed stronger relations with the development of math language and numeracy skills for younger children as compared to older children. Also, for older children math skills negatively predicted growth in their socio-emotional skills. The findings provide more insights in how language, math language and numeracy skills and socio-emotional skills co-develop in the early years and as such have important implications for interventions aimed to support children’s development.